M‐Atrial Natriuretic Peptide and Nitroglycerin in a Canine Model of Experimental Acute Hypertensive Heart Failure: Differential Actions of 2 cGMP Activating Therapeutics. Issue 1 (2nd January 2014) - McKie, Paul M.; Cataliotti, Alessandro; Ichiki, Tomoko; Sangaralingham, S. Jeson; Chen, Horng H.; Burnett, John C.
Abstract : Background: Systemic hypertension is a common characteristic in acute heart failure (HF). This increasingly recognized phenotype is commonly associated with renal dysfunction and there is an unmet need for renal enhancing therapies. In a canine model of HF and acute vasoconstrictive hypertension we characterized and compared the cardiorenal actions of M‐atrial natriuretic peptide (M‐ANP), a novel particulate guanylyl cyclase (pGC) activator, and nitroglycerin, a soluble guanylyl cyclase (sGC) activator. Methods and Results: HF was induced by rapid RV pacing (180 beats per minute) for 10 days. On day 11, hypertension was induced by continuous angiotensin II infusion. We characterized the cardiorenal and humoral actions prior to, during, and following intravenous M‐ANP (n=7), nitroglycerin (n=7), and vehicle (n=7) infusion. Mean arterial pressure (MAP) was reduced by M‐ANP (139±4 to 118±3 mm Hg, P <0.05) and nitroglycerin (137±3 to 116±4 mm Hg, P <0.05); similar findings were recorded for pulmonary wedge pressure (PCWP) with M‐ANP (12±2 to 6±2 mm Hg, P <0.05) and nitroglycerin (12±1 to 6±1 mm Hg, P <0.05). M‐ANP enhanced renal function with significant increases ( P <0.05) in glomerular filtration rate (38±4 to 53±5 mL/min), renal blood flow (132±18 to 236±23 mL/min), and natriuresis (11±4 to 689±37 mEq/min) and also inhibited aldosterone activation (32±3 to 23±2 ng/dL, P <0.05), whereas nitroglycerin had no significant ( P >0.05) effects on these renal parameters or aldosterone activation. Conclusions: Our results advance the differential cardiorenal actions of pGC (M‐ANP) and sGC (nitroglycerin) mediated cGMP activation. These distinct renal and aldosterone modulating actions make M‐ANP an attractive therapeutic for HF with concomitant hypertension, where renal protection is a key therapeutic goal.